Irregular total labellings of Cm□Cn - Tong, Chunling; Lin, Xiaohui; Yang, Yuansheng; Wang, Liping (Utilitas Mathematica, 2010)
In this paper, we show the exact values of the total edge irregularity strength and total vertex irregularity strength of the toroidal grid C m□Cn.